Transient state estimation with the Bergeron transmission line model - Naret Suyaroj (2018)
© TÜBİTAK. Transient state estimation (TSE) was used to determine the state values that have no measurement equipment placed in an electric power system with transient phenomena. Previous papers used the PI model for TSE with a short transmission line, but longer lines require the development of algorithms that include the distributed parameters of transmission lines with the Bergeron model. The test system was a 10-bus power system. The simulated transient was caused by a fault event, resulting in different persistent voltage drops that ranged from 10% to 90% at selected buses. In addition, noises were applied to evaluate the algorithm, which was defined to be normally distributed. Noise at 1%, 2%, and 3% was added to all measurements. The results showed that the developed TSE provided good estimation at the locations that had no measurement equipment for distributed transmission lines.